Pengembangan Media Permainan Ular Tangga untuk Meningkatkan Pemahaman Peserta Didik pada Keragaman Pakaian Adat Daerah - Mega Damayanti; Zerri Rahman Hakim; Reksa Adya Pribadi; Sigit Setiawan (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
The development of this research media was used to study the diversity of regional traditional clothing which was given the name "LAGA PATI (Indonesian Traditional Clothing Snakes and Ladders)" for class IV-B students at SDN Pluit 03. The aim of this research was to obtain information regarding teacher involvement in the development process learning media for the snakes and ladders game, information regarding students' responses to the learning media for the snakes and ladders game, information about increasing students' understanding of the diversity of regional traditional clothing after using the learning media for the snakes and ladders game, and information about the feasibility of learning media for the snakes and ladders game. This research uses the R&D (Research and Development) research method using the 4D development model (define, design, develop, disseminate). Collecting data in this study using observation, interviews, questionnaires, tests and documentation. The results of this research show that (1) Involving class teachers can help students to find learning style characteristics that suit their needs; (2) The response of class IV-B students at SDN Pluit 03 has an impact on the social aspects and attitudes of students; (3) The understanding of class IV-B students at SDN Pluit 03 has increased with an average pre-test result of 59 in the "Needs Guidance" category, increasing after the post-test obtained an average of 98 in the "Very Good" category, and ( 4) The average expert validation test results obtained a feasibility percentage score of 90.75% in the "Very Eligible" category.